Beery VMI performance in autism spectrum disorder. Issue 7 (2nd October 2016) - Green, Ryan R.; Bigler, Erin D.; Froehlich, Alyson; Prigge, Molly B. D.; Travers, Brittany G.; Cariello, Annahir N.; Anderson, Jeffrey S.; Zielinski, Brandon A.; Alexander, Andrew; Lange, Nicholas; Lainhart, Janet E.
Abstract : Few studies have examined the visuomotor integration (VMI) abilities of individuals with autism spectrum disorder (ASD). An all-male sample consisting of 56 ASD participants (ages 3–23 years) and 36 typically developing (TD) participants (ages 4–26 years) completed the Beery-Buktenica Developmental Test of Visual-Motor Integration (Beery VMI) as part of a larger neuropsychological battery. Participants were also administered standardized measures of intellectual functioning and the Social Responsiveness Scale (SRS), which assesses autism and autism-like traits. The ASD group performed significantly lower on the Beery VMI and on all IQ measures compared to the TD group. VMI performance was significantly correlated with full scale IQ (FSIQ), performance IQ (PIQ), and verbal IQ (VIQ) in the TD group only. However, when FSIQ was taken into account, no significant Beery VMI differences between groups were observed. Only one TD participant scored 1.5 standard deviations ( SD s) below the Beery VMI normative sample mean, in comparison to 21% of the ASD sample. As expected, the ASD group was rated as having significantly higher levels of social impairment on the SRS compared to the TD group across all major domains. However, level of functioning on the SRS was not associated with Berry VMI performance. These findings demonstrate that a substantial number of individuals with ASD experience difficulties compared to TD in performing VMI-related tasks, and that VMI is likely affected by general cognitive ability. The fact that lowered Beery VMI performance occurred only within a subset of individuals with ASD and did not correlate with SRS would indicate that visuomotor deficits are not a core feature of ASD, even though they present at a higher rate of impairment than observed in TD participants.